Eligibility of Student Worksheets (LKM) Based on PJBL-Immers to Train Students' Creative Ecoliteracy: Kelayakan Lembar Kerja Mahasiswa (LKM) Berbasis PJBL Immers untuk melatihkan ekoliterasi kreativ Mahasiswa - Wulandari , Fitria Eka; Ardiansyah , Syahrul; Wulandari , Ria (Procedia of Social Sciences and Humanities, 2022)
This study aims to determine the feasibility of LKPD in increasing students' creative ecoliteracy. This research is a development research with a 4D development model where the validation on the LKPD uses construct validation which is validated by 2 competent experts in the midwife. The feasibility of the MFI includes the validity and reliability of the MFI which is measured using the MFI validation questionnaire sheet instrument. The validation results show that the MFI has an average score of 3.4 (valid category), with a reliability score of 0.86 (real category). The research data were analyzed descriptively and quantitatively. Based on the results of the study, it can be concluded that the LKM based on Project base learning – Immers to train students' creative ecoliteracy that was developed is valid, reliable.